A Review of Araeopidius monachus (LeConte, 1874) (Coleoptera: Dryopoidea: Ptilodactylidae), with Main Emphasis on Its Biology and Ecology - William D. Shepard; Robin Kundrata (Diversity, 2023)
Araeopidius monachus (LeConte, 1874) is the only species in the subfamily Araeopidiinae within the beetle family Ptilodactylidae. Its geographic distribution is mainly along the western coast of North America, where adults are uncommon. A diagnosis is provided along with detailed collection records highlighting its seasonality, elevational range, plant associations, and collection methods. Collection records from larvae and adults indicate a three-year life cycle. Digestive tract dissections show that the larvae consume woody material while the adults probably do not feed. Additionally, we briefly discuss the problems and prospects for research of this enigmatic species.